Grain refinement and mechanical properties enhancement on inclusion of Al2O3 in AA 7017 alloy synthesized by mechanical alloying (MA) and hot pressing (HP). (December 2022) - Prashanth, M.; Karunanithi, R.; Sivasankaran, S.; Villarejo, Luis Pérez
Abstract: Present research work aimed to study the volume percentage of Al2 O3 (5 %, 10 % and 20 %) and milling time (0, 5, 10, 15 and 20 h) on the morphology, phase formation and mechanical behavior of nanocomposite. The milled nanocomposite powder and hot-consolidated samples (500 MPa and 400 °C ) were characterized using PSA, XRD, SEM and TEM. The grain structure, grain size and elemental composition were examined using HRSEM and EDS. The TEM results confirmed the formation of nanocomposite nature of milled powder samples in which 20 h milled powders produced the crystallite size of 15.56 ± 1.05 nm, 15.28 ± 1.11 nm and 15.61 ± 1.20 nm for 5 %, 10 %, and 20 % Al2 O3 reinforced samples, respectively. The hot-consolidated TEM samples were collected at 10 vol% of Al2 O3 reinforcement due to the higher mechanical properties. The developed nanocomposite samples exhibited higher hardness (152–250 VHN) and compressive stress (501–893 MPa) when reinforced with 10 vol% of Al2 O3 compared to that of 5 vol% Al2 O3 and 20 vol% Al2 O3 . The improvement in the hardness and compressive strength of the specimens was due to the variation in the morphology of the specimen and the homogeneous distribution of the Al2 O3 reinforcement. The contribution of the strengthening mechanism to the total strength of the specimen was studied for 10 vol% of Al2 O3 reinforcement for different milling times. Graphical Abstract: ga1 Highlights: Manufactured AA 7017/Al2 O3 nanocomposites by Mechanical alloying and hot pressing. Al2 O3 particles produced a synergistic strengthening effect on the mechanical properties. Bulk specimens have homogeneous, refined microstructures, and excellent properties. The presence of MgZn2 has further promotes the strengthening of the nanocomposites.